Modified Ti-MWW Zeolite as a Highly Efficient Catalyst for the Cyclopentene Epoxidation Reaction - Tong, Wen; Yin, Jinpeng; Ding, Luoyi; Xu, Hao; Wu, Peng (Frontiers in Chemistry, 2020)
The liquid-phase epoxidation of cyclopentene (CPE) was performed in the Ti-zeolite/H2O2 catalytic system for the clean synthesis of cyclopentene oxide. Among all the Ti-zeolites (Ti-Beta, Ti-MOR, Ti-MCM-68, TS-1, TS-2 and Ti-MWW) investigated in the present study, Ti-MWW provided relatively lower CPE conversion of 13% due to the diffusion constrains, but higher CPO selectivity of 99.5%. The catalytic performance of Ti-MWW was significantly enhanced by piperidine (PI) treatment, with the CPE conversion and CPO selectivity increased to 97.8% and 99.9%, respectively. The structural rearrangement upon PI treatment converted 3-dimensional (3D) MWW structure to 2D lamellar one, which enlarged the interlayer space and greatly alleviated the diffusion constrains of cyclic cyclopentene. Furthermore, the newly constructed “open site” six-coordinated Ti active sites with PI as the ligand exhibited higher catalytic activity. The two factors contributed to more significant enhancement of the activity upon PI-assisted structural arrangement compared to the cases in linear alkenes.